Given two functions, we can combine them in such a way so that the outputs of one function become the inputs of the other. ... 3, right parenthesis first and then substitute that result into f f ff to find our answer. ..... Problem 1 ..... end{aligned} (h∘g)(x)=h(g(x))=(g(x))2−2(g(x))=(x+4)2−2(x+4)=x2+8x+16−2x−8=x2+6x+8Define.
Answer:
I thinks it's that last one
Answer: something
Step-by-step explanation:
Cant see the attatchment
Answer:
the larger number is 69
the smaller number is 16
Step-by-step explanation:
x is the smaller number
y is the larger number
x + y = 85
y - 4x = 5
y = 5 + 4x
x + 5 + 4x = 85
5x = 80
x = 16
y = 69